The infancy of core-collapse supernova remnants - Gabler, Michael; Wongwathanarat, Annop; Janka, Hans-Thomas (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT We present 3D hydrodynamic simulations of neutrino-driven supernovae (SNe) with the Prometheus-HotB code, evolving the asymmetrically expanding ejecta from shock breakout until they reach the homologous expansion phase after roughly one year. Our calculations continue the simulations for two red supergiant and two blue supergiant progenitors by Wongwathanarat et al., who investigated the growth of explosion asymmetries produced by hydrodynamic instabilities during the first second of the explosion and their later fragmentation by Rayleigh–Taylor instabilities. We focus on the late time acceleration and inflation of the ejecta caused by the heating due to the radioactive decay of 56Ni to 56Fe and by a new outward-moving shock, which forms when the reverse shock from the He/H-shell interface compresses the central part of the ejecta. The mean velocities of the iron-rich ejecta increase between 100 and 350 km s−1 (∼8–30 per cent), and the fastest 1 per cent of the iron accelerates by up to ∼1000 km s−1 (∼20–25 per cent). This ‘Ni-bubble effect’, known from 1D models, accelerates the bulk of the nickel in our 3D models and causes an inflation of the initially overdense Ni-rich clumps, which leads to underdense, extended fingers, enveloped by overdense skins of compressed surrounding matter. We also provide volume and surface filling factors as well as a spherical harmonics analysis to characterize the spectrum of Ni-clump sizes quantitatively. Three of our four models give volume filling factors larger than 0.3, consistent with what is suggested for SN 1987A by observations.